Solubility, particle formation and immune display of trimers of major capsid protein 7 of African horsesickness virus fused with enhanced green fluorescent protein - Huismans, H. (Henk), 1942- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.